AN AGE IDENTITY CONSTRUCTION IN THE 2024 INDONESIAN PRESIDENTIAL ELECTION DISCOURSE: AN IDENTITY POLITICS REVIEW - Athifah Zukhruf Nisabaha; Abrian, Rizky (Faculty of Letters Universitas Balikpapan, 2024)
This research examines the construction of age identity in the discourse of presidential candidates and vice presidential candidates in preparation for the 2024 presidential and vice presidential elections in Indonesia. This research uses Stuart Hall’s identity politics to understand how age identities are expressed, debated and manipulated in political discourse regarding the age limits for presidential and vice presidential candidates. This research uses descriptive qualitative method accompanied by secondary data sources as references. The data obtained involved analysis of texts from various media sources, such as speeches, news coverage, and political statements related to the 2024 presidential and vice presidential elections. This research will focus on the use of language and rhetoric related to the age of the candidates in an effort to shape public opinion, gain political support, and construct their age identity. Keywords: Election, Identity Politics, Stuart Hall